2014
DOI: 10.1371/journal.pone.0102891
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor-Induced Conformational Stabilization and Structural Alteration of a Mip-Like Peptidyl Prolyl cis-trans Isomerase and Its C-Terminal Domain

Abstract: FKBP22, an Escherichia coli-encoded PPIase (peptidyl-prolyl cis-trans isomerase) enzyme, shares substantial identity with the Mip-like pathogenic factors, caries two domains, exists as a dimer in solution and binds some immunosuppressive drugs (such as FK506 and rapamycin) using its C-terminal domain (CTD). To understand the effects of these drugs on the structure and stability of the Mip-like proteins, rFKBP22 (a chimeric FKBP22) and CTD+ (a CTD variant) have been studied in the presence and absence of rapamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 56 publications
(93 reference statements)
0
30
0
Order By: Relevance
“…The resulting 593 bp DNA fragment was cloned to plasmid pET28a (Novagen) using a standard method [9,10]. The yielded plasmid that carries no mutation in the cloned DNA insert was designated as p1350.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting 593 bp DNA fragment was cloned to plasmid pET28a (Novagen) using a standard method [9,10]. The yielded plasmid that carries no mutation in the cloned DNA insert was designated as p1350.…”
Section: Methodsmentioning
confidence: 99%
“…The cyclosporin A binding affinity (Kd) of rCyp was determined by a procedure as followed to find out the rapamycin binding affinity of a recombinant FKBP22 [10]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPIase activity of rCyp (120 nM) was evaluated by RNase T1 (ribonuclease T1) refolding assay as reported [29, 42]. Previously, our modeling study indicated that one S. aureus Cyp molecule binds to one molecule of CsA [42].…”
Section: Methodsmentioning
confidence: 99%
“…The unfolding of rCyp and rCyp-CsA were also monitored by a standard transverse urea gradient gel electrophoresis (TUGE) with minor modifications [29, 51, 61]. Briefly, a gel having a 10 - 7% acrylamide gradient and a 0 - 8 M urea gradient was made using a 10% acrylamide solution and a 7% acrylamide solution containing 8 M urea.…”
Section: Methodsmentioning
confidence: 99%